Studying business at university : everything you need to know - McLean, Patricia; Tatnall, Arthur (St Leonards, N.S.W : Allen and Unwin, 2000)
Learning to be a university student. Learning as you go. Finding time to study. How to remember what you've learned. New skills: lectures, tutorials and seminars. New skills: reading. New skills: writing for business. Specific writing requirements: reports. Exams in business. Oral presentations. When thing go wrong. Further study or professional life.
Keywords: Business; Report writing; Time management; Report writing; Study skills -- Australia; Time management; Business education -- Australia